Effects caused by chlortetracycline and oxytetracycline in anaerobic digestion treatment of real piggery wastewater: Treatment efficiency and bacterial diversity. (18th March 2020) - Chen, Junfeng; Yang, Yuewei; Liu, Yanyan; Tang, Meizhen; Wang, Renjun; Hu, Hanwen; Wang, Hongying; Yang, Pingping; Xue, Hanhan; Zhang, Xiao
Abstract: The treatment efficiency and bacterial diversity caused by chlortetracycline (CTC) and oxytetracycline (OTC) in anaerobic digestion treatment of real piggery wastewater were studied by polymerase chain reaction - denaturing gradient gel electrophoresis (PCR-DGGE) and real-time PCR. The COD removal efficiency and methane production were inhibited with the increasing concentration of CTC and OTC. The antagonism of CTC and OTC on methane production was observed, the inhibition rate was expanded to 55.46% from 18.34%; antagonism and enhancement were observed on inhibition rate of COD removal efficiency, and the inhibition rate was expanded to 24.84% from 4.16%. The bacterial diversity and similarities of each group were decreased with the increasing concentration of CTC and OTC. The identified species Thermotogae bacterium, Bacteroidetes bacterium, Chloroflexi bacterium, Eubacterium, Mesophilic bacterium, etc. were beneficial for COD removal and biodegradation of CTC and OTC. The quantitative fluorescence analysis was opposite to the rule of bacterial diversity by real-time PCR. Graphical abstract: Image 1 Highlights: OTC and CTC inhibited COD removal efficiency and methane production. Antagonistic effect of CTC and OTC acted upon methane production. Antagonism and enhancement acted on inhibition rate of COD removal efficiency. Bacterial diversity and similarities decreased with the increasing of CTC and OTC. Copy number of 16S rRNA increased with the increasing of CTC and OTC.